The psychodynamics of abnormal behavior - Brown, J. F; Menninger, Karl A (McGraw-Hill Book Company, 1940)
The publication focuses on behaviour and personality from the point of view of psychopathology. Intended for professional public.
McGraw-Hill publications in psychology
Keywords: osobnost; duševní poruchy; Mental Disorders; chování; behaviorální vědy; Personality; psychopatologie; psychiatrie; Behavior; Psychopathology